A study of interfaith issues between Muslims and Christians in Malaysia - Roslizawati Mohd Ramly (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, Internatonal Islamic University Malaysia, 2019)
Recently, interfaith issues such as apostasy and kalimah Allah have generated religious tension between Muslims and Christians in Malaysia. This is largely because both parties claim that the issues are affecting their religions and the right to practice them in a negative manner. The lack of sensitivities, tolerance and understanding in dealing with the issues to some extent is tainting the Muslims' and Christians' relations in this country, as they have brought about public protests, inflammatory public debate and attacks on mosques and churches. Hence, this study attempted to investigate the Muslim and Christian leaders' views on the issue of Muslim conversion and kalimah Allah, and why and how the issues are affecting Muslim-Christian relations in Malaysia. The study adopted and adapted the principles of meta-religion as an objective framework for conducting and analysing the research data. In order to acquire the firsthand data, the researcher interviewed 16 informants from among the Muslim and Christian religious leaders. The study found that these interfaith issues are responsible for generating conflict between Muslims and Christians, as they have brought disparity in the interpretations of religious freedom, the right of conversion, and the right of using kalimah Allah. Upon using the meta-religion principles as a standard for analyzing the issues, it is found that there are logical explanations as to why there should be limited freedom in religion, conversion and the use of kalimah Allah.